Pengaruh Kepuasan & Motivasi Kerja Terhadap Perilaku Organisasi - Renata Aulia Zahra Hapsari; Satrio Habibullah; Sentot Imam Wahjono (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the relationship between job satisfaction, work motivation, and organizational behavior through a literature review approach. The analysis reveals that high job satisfaction—reflected in satisfaction with salary, job roles, coworker relations, promotion opportunities, and supervision—significantly contributes to positive employee behavior within the organization. Meanwhile, strong work motivation, both intrinsic and extrinsic, encourages performance enhancement and work engagement. These two variables complement each other in shaping Organizational Citizenship Behavior (OCB), which supports organizational productivity and effectiveness. The study emphasizes the crucial role of managers in fostering a supportive work environment through fair reward systems and effective communication. These findings provide both theoretical and practical contributions to the development of adaptive and sustainable human resource management strategies.